Combined Inhibitor Free‐Energy Landscape and Structural Analysis Reports on the Mannosidase Conformational Coordinate1. Issue 4 (11th December 2013) - Williams, Rohan J.; Iglesias‐Fernández, Javier; Stepper, Judith; Jackson, Adam; Thompson, Andrew J.; Lowe, Elisabeth C.; White, Jonathan M.; Gilbert, Harry J.; Rovira, Carme; Davies, Gideon J.; Williams, Spencer J.
Abstract Mannosidases catalyze the hydrolysis of a diverse range of polysaccharides and glycoconjugates, and the various sequence‐based mannosidase families have evolved ingenious strategies to overcome the stereoelectronic challenges of mannoside chemistry. Using a combination of computational chemistry, inhibitor design and synthesis, and X‐ray crystallography of inhibitor/enzyme complexes, it is demonstrated that mannoimidazole‐type inhibitors are energetically poised to report faithfully on mannosidase transition‐state conformation, and provide direct evidence for the conformational itinerary used by diverse mannosidases, including β‐mannanases from families GH26 and GH113. Isofagomine‐type inhibitors are poor mimics of transition‐state conformation, owing to the high energy barriers that must be crossed to attain mechanistically relevant conformations, however, these sugar‐shaped heterocycles allow the acquisition of ternary complexes that span the active site, thus providing valuable insight into active‐site residues involved in substrate recognition.